OP-10 Gut microbiota dysbiosis as a driver of inflammation in Ocular Mucous Membrane Pemphigoid. (26th May 2022) - Rauz, Saaeha; Low, Liying; Suleiman, Kusy; Bassilious, Kerolos; Rossiter, Amanda; Acharjee, Animesh; Loman, Nicholas; Murray, Philip I; Wallace, Graham R
Abstract : *Correspondence - Saaeha Rauz: s.rauz@bham.ac.uk Objectives: Mucous Membrane Pemphigoid is an orphan multi-system autoimmune scarring disease involving mucosal sites, including the ocular surface (OcMMP) and gut. The gut microbiome plays a critical role in the development of the immune system. This study examines the relationship between gut microbiome diversity and ocular inflammation in patients with OcMMP. Methods and Analysis: Gut microbiome profiles between OcMMP patients (n=49) and healthy controls (n=40) were compared by extracting DNA from faecal samples and amplified for the V4 region of the 16S rRNA gene followed by Illumina Miseq platform sequencing. Sequencing reads were processed using the bioinformatics pipeline available in the mothur v.1.44.1 software. Results: Using multivariable model and adjustment for participant factors, OcMMP cohort was found to be associated with lower number of operational taxonomic units (OTUs) and Shannon Diversity Index when compared to healthy controls. OcMMP OTUs were found to be significantly correlated with both the bulbar conjunctival inflammation score (p=0.03) and the current use of systemic immunotherapy (p=0.02). Linear discriminant analysis effect size scores found Streptococcus and Lachnoclostridium enriched in OcMMP. By contrast, healthy controls were enriched with Oxalobacter, Clostridia uncultured genus-level group (UCG) 014, Christensenellaceae R-7 group and butyrate-producing bacteria such as Ruminococcus, Lachnospiraceae, Coprococcus, Roseburia, Oscillospiraceae UCG 003, 005, NK4A214 group (Log10 LDA score <2, FDR-adjusted p<0.05). Conclusion: In conclusion, OcMMP patients have gut dysbiosis that correlated with bulbar conjunctival inflammation and the use of systemic immunotherapies. This provides a framework for future longitudinal deep phenotyping studies on the role of the gut microbiome in the pathogenesis of OcMMP. Reference: Low L, Suleiman K, Shamdas M, Bassilious K, Poonit N, Rossiter AE, Acharjee A, Loman N, Murray PI, Wallace GR, Rauz S. Gut dysbiosis in ocular mucous membrane pemphigoid. Front. Cell. Infect. Microbiol. 2022;12 :780354. https://doi.org/10.3389/fcimb.2022.780354